REGULATING THE FLOW: LIQUIDITY RISK IN WAEMU BANKING – AN IN-DEPTH ANALYSIS - Prao, Dr. Seraphine; Anzara, Fabrice (Economics and Statistics Research Journal (ESRJ), 2023)
The banking sector's role in allocating resources to investment projects is pivotal in developing economies. Banks transform short-term deposits into long-term loans, a process laden with responsibility and risk. Liquidity risk, characterized by a bank's inability to meet short-term commitments, poses a significant threat to its financial stability and reputation. This study delves into the impact of banking regulations on liquidity risk, a topic of contentious debate in the literature.